2018
DOI: 10.1111/adj.12660
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of the midwifery initiated oral health‐dental service program: perceptions of pregnant women

Abstract: BackgroundPregnant women in Australia seldom seek dental care and are unaware of its importance. To address these gaps the midwifery‐initiated oral health dental service (MIOH‐DS) program was comprehensive trialled and found effective. The aim of this study was to undertake a process evaluation of the MIOH‐DS using the perspectives of pregnant women who participated in the trial.MethodsA qualitative research design was utilized, whereby content analysis was undertaken on data from 11 semi‐structured interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
0
16
0
2
Order By: Relevance
“…The process evaluation showed that the program is feasible and could be scaled up in‐line with the national oral health plan; however, challenges exist with regard to providing a model that can be supported by public and private dental professionals. The study findings along with the perspectives of women and midwives will inform the overall scalability and implementation of the program.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process evaluation showed that the program is feasible and could be scaled up in‐line with the national oral health plan; however, challenges exist with regard to providing a model that can be supported by public and private dental professionals. The study findings along with the perspectives of women and midwives will inform the overall scalability and implementation of the program.…”
Section: Resultsmentioning
confidence: 99%
“…This study describes the process evaluation of the MIOH‐DS program from the perspectives of the dental staff who delivered the dental intervention in the trial. The perceptions of the midwives and pregnant women who were part of the program have been detailed elsewhere …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ainda existe a crença de que em cada gestação a mulher perde um dente; que a gravidez causa cárie dentária; que a gestante não pode receber tratamento odontológico como anestesia e muitos outros mitos 23 . Muitas mulheres que precisam de tratamento não procuraram o cirurgião-dentista 24,25 e tem consequências, nesta fase, das mais variadas, como progressão de cárie preexistente em um elemento dental até parto prematuro ou baixo peso ao nascer 5,12 .…”
Section: Discussionunclassified
“…In this light, midwives can play an important role in providing antenatal oral health screening and education, as well as dental referrals [40,46]. Furthermore, recent surveys have also reported that Australian women are positive towards receiving oral health advice from midwives during pregnancy [38,47].…”
Section: Introductionmentioning
confidence: 99%